Effects of different cooking methods on isoflavone content in Malaysian soy-based dishes - Hasnah Haron,; Tasneem Shaari,; Chan, Boon Keng (Penerbit Universiti Kebangsaan Malaysia, 2016)
Soy-based products are one of famous raw ingredients used in the preparation of Asian cuisines. These soy-based products are good source of isoflavones. This study was carried out to observe the effects of different cooking methods on isoflavone content in soy-based products. A total of eight Malaysian dishes prepared using soy-based products with different cooking methods was selected as samples for this study. Daidzein and genestein contents in raw and cooked soy-based products were both quantified using high performance liquid chromatography (HPLC). The results showed that dishes containing tempe as ingredients had significantly higher (p<0.05) amount of isoflavone content, in both raw and cooked forms, as compared to those prepared from other types of soy-based products when based on dry and wet. In conclusion, the isoflavone content was significantly reduced (p<0.05) in some cooked soy-based products (tempe (TSS and ML), fu jook (ML) and firm tofu (FTC)) based on dry weight as compared with the raw ones. However, the correlations between isoflavone content with cooking methods, durations and temperatures were not significant (p>0.05) in this study.